Raman Spectroscopic Study of Carbon Nanotubes Prepared Using Fe/ZnO-Palm Olein-Chemical Vapour Deposition. (9th February 2012) - Mohd Zobir, Syazwan Afif; Abu Bakar, Suriani; Abdullah, Saifollah; Zainal, Zulkarnain; Sarijo, Siti Halimah; Rusop, Mohamad
Abstract : Multiwalled carbon nanotubes (MWCNTs) were synthesized using Fe/ZnO catalyst by a dual-furnace thermal chemical vapor deposition (CVD) method at 800–100 0 ° C using nitrogen gas with a constant flow rate of 150 sccm/min as a gas carrier. Palm olein (PO), ferrocene in the presence of 0.05 M zinc nitrate, and a p-type silicon wafer were used as carbon source, catalyst precursor, and sample target, respectively. D, G, and G ′ bands were observed at 1336–1364, 1559–1680, and 2667–2682 cm - 1, respectively. Carbon nanotubes (CNTs) with the highest degree of crystallinity were obtained at around 800 0 ° C, and the smallest diameter of about 2 nm was deposited on the silicon substrate at 100 0 ° C.